Attention Deficit Hyperactivity Disorder Erroneously Diagnosed and Treated as Bipolar Disorder - Atmaca, Murad; Ozler, Sinan; Topuz, Mehtap; Goldstein, Sam (Sage Publications Inc, 2009)
Objective: There is a dearth of literature on patients erroneously diagnosed and treated for bipolar disorder. Method: The authors report a case of an adult with attention deficit hyperactivity disorder erroneously diagnosed and treated for bipolar disorder for 6 years. At that point, methylphenidate was initiated. The patient was judged to be a good treatment responder with improvements noted in the clinical global impressions severity scale. It was seen that the improvement was maintained at a 6-month follow-up. Conclusion: The present case reflects the importance of careful differential diagnosis when evaluating for bipolar disorder. (J. of Att. Dis. 2009; 13(2) 197-198)
Keywords: ADHD; case; methylphenidate; bipolar disorder